Humanism as a New Paradigm in 21st Century Criminal Law Reform - Dana, I Kadek Prajadwiva Baskara; Sudharma, Kadek Januarsa Adi; Kurniawan, I Gede Agus (Faculty of Law, Universitas Pekalongan, 2024)
21st century criminal law is undergoing a paradigmatic transformation marked by a shift from a retributive paradigm toward a humanistic one. This new paradigm positions human beings as the central subject of law, aiming to create a criminal justice system grounded in humanity, substantive justice, and the protection of human dignity. This study seeks to analyze the construction of humanistic principles as a new paradigm in criminal law and to examine the extent to which Indonesian criminal law—through the new Criminal Code (KUHP)—has adopted restorative and rehabilitative justice values within its legislative framework and enforcement practices. The research employs a normative legal method using a conceptual approach, analyzing primary legal materials such as the 2023 KUHP, secondary materials including academic literature, and tertiary sources such as legal encyclopedias. The data are examined through a descriptive-analytical method to understand the interrelation between legal norms and humanistic values. The findings reveal that the new KUHP has incorporated the principles of humanism, as reflected in the provisions concerning the purposes of punishment, the prohibition of degrading treatment, and the application of restorative justice principles. Nevertheless, its implementation continues to face structural and cultural challenges within law enforcement institutions. This study contributes scientifically by offering a philosophical and normative perspective on humanism as the foundation for national criminal law reform that is just, civilized, and oriented toward social restoration